SURVIVAL STRATEGIES OF WOMEN FISHER IN MUARA SELOTONG - Riadi Syafutra Siregar (Universitas Negeri Medan, 2021)
This paper aims to identify and describe the survival strategies of women fishers in meeting the needs of family life in Muara Selotong and the distribution of marine products. In their role, women fishers do not only play a role in the domestic space but also participate to fulfill and increase income, so that they are sufficient for the family economy. This research uses a qualitative method with an ethnographic approach, research techniques include; participant observer and in-depth interviews. The results of the field research show that in helping the family's economy, women fisher in Muara Selotong work looking for shellfish, crabs and helping their husbands in looking for fish and shrimp. The technique of looking for shells and crabs uses the traditional way, namely by using a “Gancu” tool and watching the tides. For the sake of getting additional economics, some dare to do this work, even though they are not good at swimming. Economic demands and low levels of education are the main reasons for women to participate in helping the family economy because the income earned by men as heads of households is deemed insufficient. Women also have wider access and networks than men to distribute marine products. because women take on roles from the production stage to distribution in the market. It can be seen that the dual role of women is very helpful to meet the needs of the family.